2006
DOI: 10.1152/ajpregu.00646.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates elicitation of reflex swallowing from the pharynx in rats

Abstract: . Nitric oxide modulates elicitation of reflex swallowing from the pharynx in rats. Am J Physiol Regul Integr Comp Physiol 291: R651-R656, 2006. First published April 6, 2006 doi:10.1152/ajpregu.00646.2005.-The pharynx is very important for elicitation of reflex swallowing. The region of the pharynx is innervated by the pharyngeal branch of the glossopharyngeal nerve (GPNph). Nitric oxide (NO) plays an important role in various physiological functions. The purpose of this study is to investigate the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The recto-anal function in the discrimination of gut content is mainly attributed to the enteric recto-anal reflex, which consists of rectal contraction and the internal relaxation of the anal sphincter. This demonstrates the importance of propulsion generated by the internal anal sphincter [11][12][13]. However, according to Bharucha (2006) both the internal and external anal sphincters are responsible for evacuative motion in the anal canal [14].…”
Section: Introductionmentioning
confidence: 89%
“…The recto-anal function in the discrimination of gut content is mainly attributed to the enteric recto-anal reflex, which consists of rectal contraction and the internal relaxation of the anal sphincter. This demonstrates the importance of propulsion generated by the internal anal sphincter [11][12][13]. However, according to Bharucha (2006) both the internal and external anal sphincters are responsible for evacuative motion in the anal canal [14].…”
Section: Introductionmentioning
confidence: 89%
“…The trachea of the animal was cannulated to maintain respiration. Bipolar enamel-coated stainless steel wire electrodes (5 mm in diameter) were inserted into the left mylohyoid muscle, recognized as "obligate muscle" involved in swallowing movements, to record its electromyographic (EMG) activity (10,11,21). Swallowing was identified by the EMG activity of the mylohyoid muscle and by visual observation of laryngeal movement.…”
Section: Methodsmentioning
confidence: 99%
“…The superior laryngeal nerve (SLN), innervating the laryngeal region, is well known to be the most important afferent nerve for initiation of reflex swallowing (2)(3)(4)(5)(6)(7)(8). Animal studies have shown that electrical stimulation of the SLN elicits reflex swallowing (7)(8)(9)(10)(11)(12)(13). On the other hand, the role of the glossopharyngeal nerve (GPN) in reflex swallowing is less well understood (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Some cues for the modulation of SS were obtained from the ''fetal swallowing'' studies in human and nonhuman fetuses [69][70][71]. Fetal swallowing that may be considered like SS develops in utero and occurs at much higher rates in comparison to adult spontaneous drinking activities [51,69,70].…”
Section: Spontaneous Swallowing (Ss) In Different Conditionsmentioning
confidence: 99%
“…NO, neural NO synthetase (NOS), angiotensin-II, and glutamate NMDA receptors are essential components in the pathways that mediate the high rate of swallowing. It is likely that other neurotransmitters (i.e., cholinergic and adrenergic) contribute to the regulation of SS in the fetus [70,71]. It was also proposed that the NMDA-NO pathway is involved in the central nervous system mechanism underlying the initiation of reflex swallow or SS [69,71,73].…”
Section: Spontaneous Swallowing (Ss) In Different Conditionsmentioning
confidence: 99%